Low cost passive monitoring of sulphur dioxide in ambient air: An effort from developing world - Maskey-Byanju, Rejina; Gewali, M. B.; Manandhar, K. (Nepal Journal of Environmental Science, 2013)
Standard sulphur dioxide (SO2) monitoring techniques require expensive instrumentation which is not easily adapted for large scale monitoring by resource limited countries. This paper presents the use of locally available relatively cheaper polyethylene tubes to be developed as passive diffusive sampler and use for monitoring of ambient sulphur dioxide using Tri-ethanolamine (TEA) as absorbent. After extraction with double distilled water, modified West-Gaeke method was used for analysis of sulphate adduct formed due to reaction of SO2 with TEA using spectrophotometer. The results are successfully compared with other standard methods. The detection limits and precision of the method as expressed as coefficient of variation are good for monitoring of SO2 in ambient air.